Effect of tannin-containing hays on enteric methane emissions and nitrogen partitioning in beef cattle. (12th July 2019) - Stewart, Elizabeth K; Beauchemin, Karen A; Dai, Xin; MacAdam, Jennifer W; Christensen, Rachael G; Villalba, Juan J
Abstract: The objective of this study was to determine whether feeding tannin-containing hays to heifers and mature beef cows influences enteric methane (CH4 ) emissions and nitrogen (N) excretion relative to feeding traditional legume and grass hays. Fifteen mature beef cows (Exp. 1) and 9 yearling heifers (Exp. 2) were each randomly assigned to treatment groups in an incomplete bock design with 2 periods and 6 types of hays with 3 hays fed each period ( n = 5 cows and 3 heifers per treatment). Groups were fed tannin-containing [birdsfoot trefoil (BFT ), sainfoin (SAN ), small burnet (SML )] or non-tannin-containing [alfalfa (ALF ), cicer milkvetch (CMV ), meadow bromegrass (MB )] hays. Each period consisted of 14 d of adjustment followed by 5 d of sample collection. Nine cows and 9 heifers were selected for the measurement of enteric CH4 emissions (sulfur hexafluoride tracer gas technique), and excretion of feces and urine, while dry matter intake (DMI) was measured for all animals. The concentration of condensed tannins in SAN and BFT was 2.5 ± 0.50% and 0.6 ± 0.09% of dry matter (DM), respectively, while SML contained hydrolyzable tannins (4.5 ± 0.55% of DM). Cows and heifers fed tannin-containing hays excreted less urinary urea N (g/d; P < 0.001) and showed lower concentrations of blood urea N (mg/dL; P < 0.001) than animals fed ALF or CMV, indicating that tannins led to a shift in route of N excretion from urine to feces. Additionally, cows fed either BFT or CMV showed the greatest percentage of retained N ( P < 0.001). Enteric CH4 yield (g/kg of DMI) from heifers ( P = 0.089) was greatest for MB, while daily CH4 production (g/d) from heifers ( P = 0.054) was least for SML. However, digestibility of crude protein was reduced for cows ( P < 0.001) and heifers ( P < 0.001) consuming SML. The results suggest that tannin-containing hays have the potential to reduce urinary urea N excretion, increase N retention, and reduce enteric CH4 emissions from beef cattle. The non-bloating tannin-free legume CMV may also reduce environmental impacts relative to ALF and MB hays by reducing N excretion in urine and increasing N retention.